Pelatihan Pembuatan Bahan Ajar Pendidikan Anak Usia Dini Berbasis Daring di Desa Pulau Permai Kecamatan Tambang Kabupaten Kampar - Chairilsyah, Daviq; Puspitasari, Enda; Febrialismanto3; Maria, Ilga (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2022)
Making and compiling teaching materials is a must for teachers to be able to present exciting learning.Tambang District is one of the sub-districts in Kampar Regency, Riau Province, that requires onlinetraining in teaching materials for early childhood. This is because many teachers still have not been ableto present exciting teaching materials when doing online learning. Teachers only tend to giveassignments to children through the WhatsApp platform media. If this condition is allowed to drag on, itmay significantly affect early childhood development. The training is carried out using an informationdiscussion approach and practicing making and preparing teaching materials. Early childhood educationteachers are guided in making and compiling teaching materials. Based on the output of IBM SPSSVer.23, it is known that tcount > t table (16.492> 2.11) and Sig (0.000 <0.05) then H0 is rejected, whichmeans that there is a significant effect of training in making online-based early childhood teachingmaterials on the teacher's ability to make teaching materials. Based on the service activities that havebeen carried out, it can be recommended that training activities for the preparation of online-based earlychildhood teaching materials are needed.